Kemampuan Aparat Pemerintah Dalam Pengelolaan Keuangan Di Desa Wanga Kecamatan Motoling Timur Kabupaten Minahasa Selatan - Sutrika Agnes Oping; Femmy Tulusan; Helly Kolondam (JURNAL ADMINISTRASI PUBLIK, 2023)
The purpose of this study was to find out how the ability of government officials in financial management in Wanga Village, East Motoling District, South Minahasa Regency. This study used qualitative research methods. By using the theory from Robert R. Katz (2008) in Moenir (2013), the results of the study show that the basic abilities that a person must have to help someone complete a job or task and achieve maximum results are technical abilities, human abilities and conceptual abilities. it has been done well, but there are still many things that must be considered, such as administrative problems where technical errors often occur, and various problems that often occur in Wanga Village financial management, and this is of course influenced by a person's technical ability to manage existing administration. Keywords: Quality, Public Service, Compliance, Taxpayer